A comprehensive comparison and accuracy of different methods to obtain mean radiant temperature in indoor environment. (1st June 2022) - Özbey, Mehmet Furkan; Turhan, Cihan
Highlights: Two calculation methods and eight assumptions on obtaining mean radiant temperature are compared via in-situ measurements. An office building in Mediterranean Warm/Cool Summer climate zone is selected as a case building. Angle factors are calculated according to the case building. Using assumptions or calculation methods to obtain the mean radiant temperature caused a Mean Absolute Percentage Error (MAPE) up to 9.1% compared to the reference method. Abstract: Thermal comfort is defined as "the state of mind which expresses satisfaction with the thermal environment" by the American Society of Heating, Refrigerating and Air Conditioning Engineers in the standard of the ASHRAE-55. Thermal comfort is affected by six main parameters which are split into two categories; personal (basic clothing insulation value and metabolic rate) and environmental (air temperature, relative humidity, air velocity, and mean radiant temperature) parameters. The mean radiant temperature is a problematic parameter in thermal comfort studies due to its complexity. The mean radiant temperature approaches are based on different techniques such as calculation methods, measurement methods, and assumptions. Although the assumptions are utilized by researchers to abstain complexity, their accuracies are uncertain. To this aim, this study purposes to find the accuracies of calculation and assumption methods by comparing with reference measurement method. An office building in a temperate climate zone is selected as a case study. Two calculation methods and eight assumptions on obtaining mean radiant temperature are compared via in-situ measurements. The results revealed that using assumptions or calculation methods to obtain the mean radiant temperature caused a significant error compared to the reference method and researchers should consider accuracies of these methods before utilizing them in their applications.